PREDICTION OF MINE DRAINAGE QUALITY BY KINETIC TESTS - LASMARIA SIBARANI; Retno damayanti (Puslitbang tekMIRA, 2006)
Kinetic test is one of the methods to predict acid mine drainage. The test shows the acceleration of natural oxidation rate over those observed in the field. This may have the advantage of condensing time, and providing earlier insight into the potential for acid generation. Generally, kinetic test evalu- ates the changes in pH, sulfate, acidity and host of potential metals. However, the test also has high degree uncertainty. To minimize the uncertainty it needs to calibrate and validate the model of kinetic test by comparing prediction model with actual field sampling results. As field data availability for validation is limited, it is strongly suggested that researcher should make a continuous research from the prediction and the actual sampling using many methods.